DIBUJAR PARA APRENDER: POTENCIALIDADES DE LOS DIBUJOS EN LA ENSEÑANZA DE LAS IDEAS DE LEWONTIN SOBRE LAS RAZAS HUMANAS - Gastón Pérez; Luz Salatino; Leonardo González Galli (Revista de Biologia Neotropical)
While racism is widely acknowledged as a significant issue in our society, traditional genetics education often overlooks the theoretical models crucial for understanding patterns of genetic diversity in human populations—models that could help foster a critical perspective on racism. In this article, we present the findings of research conducted within classroom activities designed to teach genetic models that elucidate what contemporary biology reveals about the genetic basis of human diversity. Specifically, the research investigated the potential contributions of drawings created by high school students during an activity centered on Richard Lewontin's seminal work. This work demonstrated that, when comparing groups traditionally classified as “races,” there is more genetic variability within populations than between them. To achieve this, we analyzed the students' drawings using thematic analysis to identify categories that reflect the ideas they convey, discussing the potential of this expressive medium in teaching these concepts.